Light and Heavy Vehicle Technology - Nunney, M. J. (Newnes, 2016)
Light and Heavy Vehicle Technology, Third Edition covers the essential technology requirements of the City and Guilds Motor Vehicle Craft Studies (381) Part 2, for both light and heavy vehicles. The book discusses the reciprocating piston petrol and diesel engines with regard to their operating principles and combustion chambers and processes. The book also apprises vehicle heating and the importance of engine lubrication and cooling. Numerous examples of vehicle maintenance procedure and of diagnosing vehicle misbehavior in service are also considered. The book covers the different vehicle systems including intake and exhaust, diesel fuel injection, ignition, automatic transmission control, suspension, hydraulic brake, and electrical systems. The vehicle structure, manual and power-assisted steering, tires, road wheels and hubs, layshaft and epicyclic gearboxes, and fluid couplings and torque converters are also discussed. Students of mechanics and mechanical engineering studies will find this book invaluable.